ANGKA BANDING LIPID DI INFARK MIOKARD - Liong Boy Kurniawan; Uleng Bahrun; Darmawaty ER (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2013)
Lipid profiles are used as the regular tests which performed to predict and evaluate the risk of coronary heart disease. The routine lipid tests include total cholesterol, LDL, HDL and triglyceride level. The total cholesterol/HDL and LDL/HDL ratio are often used as predictors of coronary heart disease. This study was performed to know the lipid level and ratio by comparing the condition in myocardial infarction patients and young adult controls and to observe the percentage of their lipid level and ratio exceeding the recommended optimal value. A retrospective study was performed using secondary data of 73 myocardial infarction patients, whom hospitalized in the Intensive Cardiac Care Unit Dr. Wahidin Sudirohusodo Hospital Makassar from June 2010 to July 2011 and 21 healthy young adult as controls. The mean level of the total cholesterol, LDL, HDL, triglyceride, ratio of total cholesterol/HDL and LDL/HDL of myocardial infarction patients are compared with the control subjects were 209.99±51.70 vs 151.42±27.90 mg/dL (p=0.000), 141.18±41.92 vs 76.76±20.45 mg/dL (p=0.000), 36.96±10.47 vs 47.05±8.24 mg/dL (p=0.000), 132.27±65.67 vs 142.14±54.93 mg/dL (p=0.155), 5.99±1.71 vs 3.26±0.59 (p=0.000) and 4.06±1.45 vs 1.66±0.44 (p=0.000), respectively. It was shown that the percentage of myocardial infarction patients with total cholesterol, LDL level, total cholesterol/HDL and LDL/HDL ratio exceeding recommended optimal value were 57.53%, 63.01%, 73.97% and 86.30%, respectively. The level of total cholesterol and LDL, ratio of total cholesterol/HDL and LDL/HDL in myocardial infarction patients were significantly higher, but the HDL level was lower compared to the control subjects. The percentage of myocardial infarction patients with LDL/HDL ratio exceeding recommended optimal value was higher than the other lipid levels and ratio. Therefore, it is concluded that the LDL/HDL ratio is better in predicting coronary heart disease than other routine lipid markers.